Examen Especial al Activo Corriente de la Fábrica de Balanceados “JUANCHIPUL” del Cantón Marcabelí, Periodo 01 de Marzo- 31 de Diciembre 2022. - Ramírez Acaro, Yanela Brigith (2024)
This research titled “Special Audit of Current Assets on the “JUANCHIPUL” balanced Feed Factory in Marcabelí Canton, Period March 1st to December 31st, 2022” was carried out in accordance with the Academic Regimen Regulation to obtain the degree in Accounting and Auditing. To achieve the stablished objectives, the methodology utilized was based on the special audit process, which comprises three phases; in the first phase, known as planning, a preliminary visit was conducted to gather general information about the company and understand its activities and operations, which facilitated the drafting of the preliminary and specific planning. In the execution phase, the internal control system was evaluated to assess the risk of the examined component and compliance with current regulations. The results showed a moderate level of risk and confidence for Cash and Cash Equivalents and Inventories, and a low level of risk and high confidence for Notes Receivable and Accounts Receivable from Customers. Additionally, substantive and control procedures were applied, which allowed for the detection of findings and verification of the reliability of the balances. Finally, in the third phase, a report was prepared that disclosed these deficiencies with their respective comments and conclusions. Among the main findings were: the lack of established policies for the management, recording, and controls of Current Assets, the absence of a functions manual detailing the tasks and responsibilities of company personnel, and the lack of implementation of control activities such as cash counts, bank reconciliations, and physical inventory verifications, which evidenced inconsistencies, generating uncertainty about the accuracy of the balances. In response to these weaknesses, recommendations for the continuous improvement of the company were proposed.